Study on the Influence of Low-Price Bid Winning and General Subcontracting Management on the Unsafe Behavior Intention of Construction Workers - Yao, Jinbao; Wu, Zhaozhi; Wen, Yanan; Peng, Zixuan (Frontiers in Psychology, 2022)
In recent years, there are many reasons for the frequent safety accidents in the construction field. The most controversial and typical one firmly correlated with China’s national condition is the low price bid winning and the general subcontracting management, which probably have a great impact on the unsafe behavior intention of workers on the construction site. In order to figure out their internal relation, a quantitative statistical analysis of the unsafe behavior intentions of construction workers in the Beijing area is conducted through the on-site questionnaire considering three main variables including general subcontract management, reasonable low-cost bid winning and construction experiences. Meanwhile, the correlation, regression and mediating effects of different influencing factors are analyzed through a regressive model to quantify the impact of each variable on unsafe behavior intention of construction workers. The results show that the influence of low price bid winning on the unsafe behavior intention of on-site workers is faint, mainly because in the case of labor buyer's market, the actual salary of workers is not relevant to whether the project is awarded at a low price. However, the general subcontracting management has a great impact on the unsafe behavior intention of on-site workers. At the same time, low-price bid winning also indirectly affects the strength of general subcontracting safety management, which has an indirect impact on unsafe behavior intention of on-site workers. Generally, it is of greater significance to enhance the strength for the general subcontracting management and formulate relevant regulations to guarantee the safety of construction workers.